Financial compensation: a worker value measure. (2011)
This work examines the incidence that the system of financial compensationstructure has on the achievement of the objectives of attracting, retaining and motivatingworkers in the organization. The research is based on the possible restrictionsidentifications of the financial compensation systems in searching these objectives. It isstarting on the analysis of the labor Colombian market conditions, specifically, on joboffer and demand; on Colombian labor legislation related with salaries and wagesand other financial incentives contemplated not only in general legislation but on theorganizational behavior theory.To establish the restrictions among the signal dimensions, chronic conflict clouds werestructured. These served later as a basis to elaborate current reality tress (C.R.T), asinitial diagnosis. In addition, future reality trees (F.R.T) were considered a proposalto evaporate chronic opposing conflicts, using the proportionate analysis methodologyfor the theory of restrictions (T.O.C.)